2009
DOI: 10.1007/s00705-009-0377-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis and characterization of a tobacco mosaic virus isolate infecting balsam (Impatiens balsamina)

Abstract: The complete RNA genomic sequence of a tobacco mosaic virus isolate infecting Impatiens balsamina, designated as TMV-IM, has been determined. The genomic sequence and the predicted gene products of TMV-IM were similar to those of other members of the genus Tobamovirus. The CP ORF of TMV-IM showed sequence identities of 95.0-99.5% with the corresponding ORFs of other TMV strains. Full-length cDNA of TMV-IM was amplified by RT-PCR with a 5'-end primer harboring a T7 promoter sequence and a 3'-end TMV-specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Furthermore, no recombination among ORSV isolates is supported by analyses that were performed by Ajjikuttira et al [5], either. Recently, for members of the genus Tobamovirus, it has been shown that variation of CP sequences is limited [16][17][18][19][20][21]. For instance, in a comparison of TMV isolates from different hosts and countries, no distinct genetic variable regions of the CP could be found [17,18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, no recombination among ORSV isolates is supported by analyses that were performed by Ajjikuttira et al [5], either. Recently, for members of the genus Tobamovirus, it has been shown that variation of CP sequences is limited [16][17][18][19][20][21]. For instance, in a comparison of TMV isolates from different hosts and countries, no distinct genetic variable regions of the CP could be found [17,18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, for members of the genus Tobamovirus, it has been shown that variation of CP sequences is limited [16][17][18][19][20][21]. For instance, in a comparison of TMV isolates from different hosts and countries, no distinct genetic variable regions of the CP could be found [17,18,20,21]. In the case of Tobacco mild green mosaic virus (TMGMV) isolates from a population of N. glauca collected in Australia during 90 years, sequence analyses showed no increase in the genetic diversity among the TMGMV isolates over this period [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…TMV can be transmitted by mechanical inoculation, grafting, contact between plants and by seed, but not by any known vector (Broadbent, 1965; Hollings and Huttinga, 1976). Tobamoviruses collectively have a very wide host range and cause serious economic impact and significantly yield losses in many crops such as brassicas, cucurbits, solanaceous crops and different ornamental plants such as chrysanthemums ( Chrysanthemum indicum L.), impatiens ( Impatiens balsamina ) and petunia ( Petunia × hybrida ) (Alexandre et al, 2000; Choi et al, 2009; Kumar et al, 2011; Nassar et al, 2012). Infected plants often show different types of symptoms such as malformations, mosaic and stunting on leaves, flowers, and fruit.…”
mentioning
confidence: 99%
“…Our detailed agroinfiltration procedures are as previously described (Choi et al, 2008). A TMV-based vector expressing GFP (TMV-GFP; Rabindran et al, 2001) was prepared and inoculated onto partitioned plants as previously described (Choi et al, 2009).…”
Section: Conditions For Agroinfiltration and Virus Inoculationmentioning
confidence: 99%